1976
DOI: 10.1063/1.322388
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced changes of CuxS films and effect on CdS-CuxS solar-cell response

Abstract: Changes in the electrical sheet resistance and optical density of copper-sulfide (Cu x S) films have been measured as functions of thermal aging in air. It was found that sheet resistance (or bulk resistivity) and optical density (or absorption coefficient) both initially increase with aging, and subsequently decrease. Maximum bulk resistivity and absorption coefficient values, corresponding to the chalcocite phase of CuxS, were found to be about 0.1 !lcm and 5X 10 4 cm-I (at 1.8 eV photon energy), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…It has long been noted that Cu 2Àx S structural, electronic and optical properties evolve in time in the presence of moist air, especially at elevated temperatures. 34,36 Calculations further suggest that low-chalcocite, even when in equilibrium with bulk Cu, may favor some Cu vacancies that result in free Cu. 37 It has been hypothesized that Cu atoms at grain boundaries and free surfaces may react to form surface species while the high mobility of copper allows the resulting vacancies to cluster into djurleite units.…”
Section: Electronic Stability Under N 2 Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…It has long been noted that Cu 2Àx S structural, electronic and optical properties evolve in time in the presence of moist air, especially at elevated temperatures. 34,36 Calculations further suggest that low-chalcocite, even when in equilibrium with bulk Cu, may favor some Cu vacancies that result in free Cu. 37 It has been hypothesized that Cu atoms at grain boundaries and free surfaces may react to form surface species while the high mobility of copper allows the resulting vacancies to cluster into djurleite units.…”
Section: Electronic Stability Under N 2 Atmospherementioning
confidence: 99%
“…This is a relatively low value for Cu 2Àx S which can be correlated with the most efficient Cu 2 S devices. 36 Notably, even under the actively scrubbed nitrogen atmosphere of the glovebox the carrier concentration rises steadily, although at a rate more than an order of magnitude slower than under air exposure (note the log-log scale). In both atmospheres the addition of free charge carriers with time is best t to a power law relationship.…”
Section: Electronic Stability Under N 2 Atmospherementioning
confidence: 99%
“…7. 19 Auger analysis ͑outer most layer͒ of the heated CuS sample indicates Cu/S to be 0.9. These ratios suggest that Cu is in excess and S is relatively deficient in the CuS heated films ͑suggesting Cu ϩ1 formation͒.…”
Section: Surface Chemical Studiesmentioning
confidence: 99%
“…As an important non-toxic, earth abundant, highly p-doped semiconductor with its metal-like electrical conductivity, CuS has attracted much attention in recent years to fabricate wide range of optical and electrical devices. [29][30][31][32][33][34] Yuan et al 35 used a CuS thin film as a p-type material in dye sensitized solar cells and achieved significant photoelectric response. Wu et al 36 reported the fabrication of an efficient flexible photovoltaic device based on a Schottky junction between CuS nanotubes and ITO film.…”
Section: Introductionmentioning
confidence: 99%